Risk Management of Subsea Pipeline Integrity and Failure Prevention - Hirzi Libna Firmanullah; Silvianita; Mas Irfan Purbawanto; Yeddid Yonatan Eka Darma (International Journal of Marine Engineering Innovation and Research, 2026)
Subsea pipelines are critical offshore infrastructures for transporting oil, gas, and produced fluids, but they are exposed to structural degradation, environmental loading, and third-party interference that may lead to leakage or failure. This study evaluates subsea pipeline damage risk by integrating Fault Tree Analysis (FTA), Event Tree Analysis (ETA), and Bowtie Analysis. Risk identification classified the main hazards into pipeline structural integrity failure and third-party interference. The FTA results show that the probability of subsea pipeline damage as the top event is 0.0297492, with pipeline structural integrity failure contributing 0.0179766 and third-party interference contributing 0.0119882. The dominant basic events are failure to conduct periodic inspection, corrosion, gasket failure, emergency anchoring, and severe weather conditions. ETA was applied to assess consequence pathways after pipeline damage through six safety barriers: detection and alarm, alarm verification and decision making, emergency shutdown and isolation, pressure and inventory control, area control and secondary impact prevention, and emergency response, inspection, and repair. The results indicate that minor damage with no significant fluid release has the highest probability, whereas catastrophic loss of containment has the lowest probability but the most severe impact. Bowtie Analysis integrates the causal and consequence pathways into preventive and mitigation controls for integrity.